Relationship between Attribution disposition of Guardians of a Cerebral Palsy Child and Their Family Resilience - Park, Soon-Gil; Jun, Jung-Sook; Han, Jai-Geum (Advances in Social Sciences Research Journal, 2017)
This study concerns attribution disposition and family resilience of guardians of a child with epileptic cerebral palsy and aims to examine variables affecting disability prognosis and disability acceptance degree according to whether the children have convulsion or not. Among the guardians of children at schools for students with mental retardation located in Seoul, Ansan, Cheonan, and Daegu, attribution disposition and family resilience of 88 guardians whose child had epileptic disorder and 106 guardians whose child did not have epileptic disorder, therefore 194 guardians in total were examined. Descriptive statistics, F- test, and regression analysis were conducted. The result was that attribution to fortune, attribution to efforts, and situations of crisis predicted the degree of disability acceptance. Therefore, given that epileptic cerebral palsy is a severe disability, family resilience is not acting efficiently in the adaptation process of guardians. Thus in the special education field, family support is required to improve family resilience and promote guardians’ internal attribution of their children’s disability for positive adaptation.